Pharmacological activities and effective substances of the component-based Chinese medicine of Ginkgo biloba leaves based on serum pharmacochemistry, metabonomics and network pharmacology - Liang, Hongbao; Yao, Jingchun; Miao, Yu; Sun, Ying; Gao, Yanbing; Sun, Chenghong; Li, Rui; Xiao, He; Feng, Qun; Qin, Guofei; Lu, Xiaoyan; Liu, Zhong; et al. (Frontiers in Pharmacology, 2023)
As a potential drug candidate for the treatment of hypertension and complications, it is speculated that the component-based Chinese medicine of Ginkgo biloba leaves (GBCCM) which mainly composed of flavonoid aglycones (FAs) and terpene lactones (TLs) may have different pharmacological effects at different doses or ratios. Taking the normal mice as the study object, metabonomics was conducted by giving different doses of GBCCM. Based on the components of GBCCM absorbed into the blood, the network pharmacological prediction was carried out. By integrating the results of metabonomics and network pharmacology, predict the possible pharmacological effects of GBCCM and conduct experimental verification. It was found that 8 of the 19 compounds in GBCCM could be absorbed into the blood. GBCCM mainly affected the signal pathways of unsaturated fatty acid, pyruvate, bile acid, melanin and stem cells. It was speculated that GBCCM might have activities such as lowering blood pressure, regulating stem cell proliferation and melanogenesis. By establishing the models of mushroom tyrosinase, rat bone marrow mesenchymal stem cells (BMSCs) and spontaneously hypertensive rats (SHRs), we found that FAs and TLs showed synergistic effect in hypertension and tyrosinase models, and the optimal ratio was 3:2 (4.4 mg/kg) and 1:1 (0.4 mg/ml), respectively. As effective substances, FAs significantly promoted the proliferation of rat BMSCs on the 3rd and 5th days at the concentration of 0.2 μg/ml (P < 0.05). GBCCM showed a variety of pharmacological effects at different doses and ratios, which provided an important reference for the druggability of GBCCM.